Performance investigation of a solar powered electric car - Hossain, Md. Abir; Saiful, Abdul Majid; Sakib, Md. Nazmus; Nion, Ajmir Hossain (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.